The effect of heat treatment on the nutritional and antioxidant content of different milk types - AKBAY, TUĞBA (My University, 2022)
Heat treatments may cause some chemical and physicochemical changes in milk, although milk is a heat-stable system. Heat treatments can cause different changes in different types of milk. This study aimed to compare the effects of pasteurization and boiling on goat and cow milk's macromolecular contents, glutathione levels, and superoxide dismutase activities. The protein level of both types of milk decreased with the pasteurization process, and boiling also reduced the protein level of goat milk. Both heat treatments reduced superoxide dismutase activity and glutathione levels in both types of milk. While the boiling process did not change the cow's milk lactose level, it increased the goat milk lactose level. It was determined that pasteurization reduced the lactose level in both types of milk. Pasteurization did not change the fat level in cow milk but decreased the fat level in goat milk. In conclusion, cow milk was less affected by these heat treatments, which can be attributed to having large fat globules, high lactose concentration, and high heat resistance protein content compared to goat milk.
Keywords: Milk; Boiling; Pasteurization; Antioxidants; The Nutritional Content of Milk